Knowledge, Practices, and Nasal Carriage Rate of MRSA Amongst Dental Professionals - Mohamed A. Jaber; Wasim Kamate; Alexander Maniangat Luke; G.S. Karande (Elsevier, 2024)
ABSTRACT: Objective: Resistance of Staphylococcus aureus (S. aureus) against common antibiotics has been increasing given the rampant use of antibiotics. Methicillin-resistant S. aureus (MRSA) is particularly important because it has been reported to present in hospital-acquired as well as community-acquired infections. Our aim was to study the types and subtypes of MRSA isolated from nasal swabs taken from volunteering dental school students and to assess and analyse the knowledge of dental health care workers (DHCWs) on MRSA and prevention of its infection. Methods: A total of 100 participants, which included staff, students, and dental auxiliaries, from the School of Dental Sciences, Krishna Institute of Medical Sciences, Deemed to Be University, Karad, India, were included in the study which was conducted from June 2020 to 1 June 2021. All the participants completed a survey and underwent collection of nasal swabs. The samples were cultured and underwent microbiological and molecular analysis for MRSA. The questionnaire was sent out electronically via SurveyMonkey. Results: Sixty-three percent of the participants were female. The majority were undergraduate students (66%) and younger than 25 years (77%). The prevalence of MRSA in the sample was the MRSA type SCCmec type V (54.8%). The survey reports a lack of knowledge amongst dental students on MRSA and prevention of its infection. The majority (69%) of participants had not heard of MRSA infection and had inadequate knowledge of MRSA infection. Only 29% of the participants think that a healthy person may have MRSA without feeling ill. Eighty-five percent of the participants reported that they have written polices and guidelines to control MRSA. Eighty-five percent of the participants indicated that they are less confident in their knowledge on MRSA infection control protocols, and 94% mentioned that the dental clinics have written guidelines for hand hygiene. Conclusions: DHCWs have limited knowledge of MRSA infection, emphasising the need for appropriate clinical training. Academic institutions should promote effective infection control training to protect students, faculty, and other employees.